Egg Quality and Heavy Metal Concentrations in Meat, Eggs and Inner Organs of Laying Ducks Fed under a Conventional Feeding in Lombok, Indonesia - Indarsih, B.; MH. Tamzil; Asnawi; DK. Purnamasari (Jurnal Peternakan Integratif, 2023)
The search for alternative protein sources for duck feed is important considering its high cost. An experiment involving 100 forty-wk-old laying ducks was conducted for eight weeks to study the effects of fresh water fish (sapu-sapu fish -SSF) as single protein sources  on egg quality and heavy metal concentration. The SSF levels were 28 and 35% of the feed and the remaining constituent was rice bran with metabolizable energy approximately 2,943 and 2,934 kcal/kg, respectively. Fresh  water fish did not effect on egg quality measured except egg weight and shell thickness (63.2±0.30 to 67.9±0.22g) and shell thickness (0.50±0.04 to 0.52±0.04g) with increasing dietary SFF(P<0.05). Mean concentrations of heavy metals in local duck samples decreased in the order kidney>liver>egg>meat for Pb and liver>kidney>meat>egg for Cu. Lead concentrations in meat, eggs, liver and kidney were 1.267± 0.825, 1.311±0.737, 1.762±0.729 and 2.172±0.770 mg/kg respectively. These values were higher than the admissible amounts under the Indonesian National Standards (1.0 mg Pb/kg) and FAO (0.1 mg Pb/kg). Accumulation of Cu in the meat, eggs, liver and kidney was 12.798±4.181, 7.011±1.949, 30.165±16.561 and 14.392± 4.208 mg/kg respectively. These levels were also higher than that recommended by the European Commission. The conclusion of this study proved that feeding SSF to laying ducks raised by small farmers contained a significantly high concentration of heavy metals not appropriate for human consumption when high levels of SSF was fed